RECYCLING OF SECONDARY RAW MILK WHEY DEMINERALIZATION AFTER THE TREATMENT BY REVERSE OSMOSIS - Arthur S. Merkel; George Echer; Ivan A. Evdokimov; Andrey G. Khramtsov (Вестник Северо-Кавказского федерального университета)
The possibility and the results of laboratory studies with the use of electrodialysis removing minerals from whey have been presented. The technical parameters of the electrodialysis installation (EDR-Z) have been calculated and displayed.